Pengaruh Pertumbuhan Ekonomi, Investasi dan Indeks Pembangunan Manusia terhadap Ketimpangan Pendapatan di Indonesia - Maorencia, Queentha Monica; Marwan, Marwan (Lembaga Yasin AlSys, 2023)
The study aims to examine the extent of the influence of economic growth, domestic investment, foreign investment and human development index on income distribution inequality in Indonesia in 2018-2022. This type of research is descriptive and associative, the data used is panel data where the research was conducted in Indonesia in 2018-2022. This research uses the Eviews 12 application, the model chosen is the Fixed Effect Model. The F test shows that economic growth, domestic investment, foreign investment and human development index have a significant effect on income distribution inequality. While in the t test, economic growth and foreign investment have a negative and insignificant effect on income distribution inequality, domestic investment has a positive and insignificant effect on income distribution inequality, human development index has a significant negative effect on income distribution inequality The results of the Coefficient of Determination (R2) test found 0.968. This means that 96.8% of the dependent variable is explained by the independent variable, while 3.4% is explained by other variables outside the model or not included in this study.